An Economic Evaluation of Integrated Pest Management Practices in English Cabbage Production in Cameron Highlands, Malaysia - Mohd Amir, Hairuddin (2006)
Anxieties about negative effects of pesticide use in developing countries have motivated the development of Integrated Pest Management (IPM) programs in these countries. In Malaysia, the IPM collaborative research support program (CRSP) was established to specifically address the widespread misuse of pesticides in cabbage vegetable cultivation in Cameron Highlands, one of the major vegetable producing regions in the country.